(untitled) (Journal of Computational Mathematics, 2018)
In this paper, the multisymplectic Fourier pseudospectral scheme for initial-boundary value problems of nonlinear Schrödinger equations with wave operator is considered. We investigate the local and global conservation properties of the multisymplectic discretization based on Fourier pseudospectral approximations. The local and global spatial conservation of energy is proved. The error estimates of local energy conservation law are also derived. Numerical experiments are presented to verify the theoretical predications.